Legal Framework for Biosphere Reserves as Learning Sites for Sustainable Development: A Comparative Analysis of Ukraine and Sweden - Elbakidze, Marine (Springer Netherlands, 2013)
The Biosphere Reserve (BR) concept aims at encouraging sustainable development (SD) towards sustainability on the ground by promoting three core functions: conservation, development, and logistic support. Sweden and Ukraine exemplify the diverse governance contexts that BRs need to cope with. We assessed how the BR concept and its core functions are captured in national legislations. The results show that the core functions are in different ways reflected in legal documents in both countries. While in Ukraine the BR concept is incorporated into legislation, in Sweden the concept is used as a soft law. In Ukraine managers desired stronger legal enforcement, while in Sweden managers avoided emphasis on legislation when collaborating with local stakeholders. Hence, BR implementation have adapted to different political cultures by development of diverse approaches. We conclude that a stronger legal support might not be needed for BRs, rather SD needs to be recognized as an integrated place-based process at multiple levels. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13280-012-0373-3) contains supplementary material, which is available to authorized users.